The Role of Soft Leadership in Achieving the Strategic Objectives of theEconomic Institution: An Applied Study of a Sample of Economic Institutions in M'sila - YOUSFI Kamal, (Journal of North African Economies, 2025)
This study aimed to shed light on soft leadership in its dimensions (vision, emotional intelligence, and communication) as a new leadership style, and to show its role in achieving the strategic Objectives of a sample of active economic institutions in M'sila, Algeria. To achieve the goal, a questionnaire was designed for the purpose of data collection. It was distributed to an intentional sample of (108) workers from different administrative levels. The results of the theoretical study showed that the application of the soft leadership style will create the appropriate work environment to achieve the desired strategic objectives of the institution. The results of the practical study also showed that there is a strong and positive correlation and effect relationship with statistical significance at the approved significance level (α≤0.05). between soft leadership and strategic Objectives. In the light of these results, the study recommended adopting the soft leadership style and enhancing its dimensions in the organizational environment because of its effective role in achieving the strategic objectives of the economic institutions under study.